DAMPAK SISTEM PEMBAYARAN SEWA KENDARAAN TRUCKING TERHADAP KEGIATAN OPERASIONAL PERUM DAMRI LOGISTIK - Sylvira Ananda Azwar; Kencana Verawati; Meliana Safitri; Anthony Costa (LOGISTIK, 2021)
This Research aims to find out the causes and impacts caused by delays in payment of trucking vehicle rentals at Perum DAMRI Logistik, especially on the company's operational activities. Data collection was carried out in 3 divisions in Perum DAMRI Logistics, namely the operational division, the financial division and the engineering division. Data collection was done by interviewing the staff on duty and making observations and observations while in the field. The data obtained is then analyzed and elaborated so as to form a relevant information. In addition to describing the results of interviews, there are some data that are processed using statistical analysis using correlation tests and simple linear regression tests. The statistical data analysis was used to determine the relationship between vehicle rental payments and operational activities and to find out what percentage of the effect was obtained from the two variables. The results of the correlation test using SPSS statistic 25 which shows that vehicle rental payments and operational activities have a positive relationship, the results of a simple linear regression test get the equation Y = 200534,257 + 0.659X. The value of R square is 0.559.